2009
DOI: 10.4103/0971-6203.51937
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure levels within timber industries in Calabar, Nigeria

Abstract: The UNSCEAR (2000) observed that there could be some exposure at work which would require regulatory control but is not really considered. This study was, therefore, set up to evaluate the effective dose in timber industries in Calabar, Nigeria to determine if the evaluated dose levels could lead to any radiological health effect in the workers, and also determine if the industries require regulatory control. The gamma ray exposure at four timber industries measured using an exposure meter were converted to ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…They concluded that the differences may be due to variations in levels of industrial activities in the area. Similar increase in environmental radioactivity in other cities in Nigeria has also been reported (Ajayi, 2001;Kuforiji et al, 2003;Arogunjo et al, 2004;Isinkaye and Ajayi 2006;Ajayi et al, 2006;Ademola, 2008;Farai et al, 2008;Farai and Ademola, 2005;Alatise et al, 2008;Inyang et al, 2009). This study involves the determination of ionizing radiation levels around bottling and pharmaceutical facilities in Ilorin metropolis with a view to assessing whether the radiation profile is within tolerable limit.…”
Section: Research Papersupporting
confidence: 60%
See 1 more Smart Citation
“…They concluded that the differences may be due to variations in levels of industrial activities in the area. Similar increase in environmental radioactivity in other cities in Nigeria has also been reported (Ajayi, 2001;Kuforiji et al, 2003;Arogunjo et al, 2004;Isinkaye and Ajayi 2006;Ajayi et al, 2006;Ademola, 2008;Farai et al, 2008;Farai and Ademola, 2005;Alatise et al, 2008;Inyang et al, 2009). This study involves the determination of ionizing radiation levels around bottling and pharmaceutical facilities in Ilorin metropolis with a view to assessing whether the radiation profile is within tolerable limit.…”
Section: Research Papersupporting
confidence: 60%
“…Industrial activities account for a significant percentage of contribution to total environmental pollution and general degradation of the natural environment that we experience today (Oke 2004;Inyang et al, 2009;EEA, 2011). Our environment contains naturally occurring radioactive materials, which spontaneously disintegrate to form stable nuclei and in the process release radiation to the environment (IAEA, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For effective monitoring, the radiation meter was placed at the gonad level of 1m above ground level with the window of the meter directed toward each site and 10 readings taken in different directions in each site and the mean recorded. Measurements of exposure levels in this investigation were taken in the afternoon between 1000 hours and 1700 hours for effective response of the meter to environmental radiation exposures within Calabar [8]. The measured mean background ionising radiation (σ) is converted to annual equivalent dose rate (HTc) using equation 1 […”
Section: Exposure Measurementmentioning
confidence: 99%
“…Wastes made up an environmental and public health nuisance in major cities all over the world. Thus, governments regard waste management as vital social service whose budgetary provision is made in line with population projections [17] . Hazards caused by such dumpsite are not only in term of odor and presence of disease causing microorganism, but can arise from the radiation emanating from such dumpsite [18] .…”
Section: Introductionmentioning
confidence: 99%